Design considerations for introducing PBL in computer engineering - Coto, Mayela (2012)
Nowadays, universities are driven to adopt pedagogical approaches that enable them to better meet the needs of the new generation of students and industry. This article presents an ongoing experience in innovating the computer engineering curriculum through a problem-based and project-oriented learning approach to develop skills such as problem solving, effective communication, teamwork and lifelong learning, which are increasingly demanded by employers and society. The investigation determined an initial set of design principles that can be used to guide an implementation strategy of the approach. The methodology allows continuous evaluation and refinement of the design. The findings so far point to a number of obstacles, from student, teachers and management, which must be overcome to achieve an effective result.